Double-blind randomised placebo-controlled trial of bolus-dose vitamin D3 supplementation in adults with asthma (ViDiAs). Issue 5 (27th February 2015) - Martineau, Adrian R; MacLaughlin, Beverley D; Hooper, Richard L; Barnes, Neil C; Jolliffe, David A; Greiller, Claire L; Kilpin, Kate; McLaughlin, David; Fletcher, Gareth; Mein, Charles A; Hoti, Mimoza; Walton, Robert; et al.
Abstract : Rationale: Asthma exacerbations are commonly precipitated by viral upper respiratory infections (URIs). Vitamin D insufficiency associates with susceptibility to URI in patients with asthma. Trials of vitamin D in adults with asthma with incidence of exacerbation and URI as primary outcome are lacking. Objective: To conduct a randomised controlled trial of vitamin D3 supplementation for the prevention of asthma exacerbation and URI (coprimary outcomes). Measurements and methods: 250 adults with asthma in London, UK were allocated to receive six 2-monthly oral doses of 3 mg vitamin D3 (n=125) or placebo (n=125) over 1 year. Secondary outcomes included asthma control test and St George's Respiratory Questionnaire scores, fractional exhaled nitric oxide and concentrations of inflammatory markers in induced sputum. Subgroup analyses were performed to determine whether effects of supplementation were modified by baseline vitamin D status or genotype for 34 single nucleotide polymorphisms in 11 vitamin D pathway genes. Main results: 206/250 participants (82%) were vitamin D insufficient at baseline. Vitamin D3 did not influence time to first severe exacerbation (adjusted HR 1.02, 95% CI 0.69 to 1.53, p=0.91) or first URI (adjusted HR 0.87, 95% CI 0.64 to 1.16, p=0.34). No clinically important effect of vitamin D3 was seen on any of the secondary outcomes listed above. The influence of vitamin D3 on coprimary outcomes was not modified by baseline vitamin D status or genotype. Conclusions: Bolus-dose vitamin D3 supplementation did not influence time to exacerbation or URI in a population of adults with asthma with a high prevalence of baseline vitamin D insufficiency. Trial registration number: NCT00978315 (ClinicalTrials.gov).